2005
DOI: 10.1039/b508499g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anti-microbial activities and anti-electrostatic properties of phosphonium-based ionic liquids

Abstract: A range of phosphonium ionic liquids having the generic formula [PR 3 R9]X (R and R9 are alkyl groups; X is halide, trifluoromethanesulfonate, bis(trifluoromethylsulfonyl)imide, nitrate, dialkylphosphinate, dicyanamide, decanoate, tetrafluoroborate, hexafluorophosphate, or diisobutyldithiophosphinate have been prepared, characterised, and tested for anti-microbial activity and anti-electrostatic properties. Within this group of phosphonium salts, in contrast to their 1-alkyl-3-methylimidazolium analogues, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(107 citation statements)
references
References 56 publications
3
103
0
1
Order By: Relevance
“…In fact only recently, have specific ILs with biologically active ions been prepared and shown to retain their biological activity; specifically, IL salts of anti-bacterial quaternary ammonium cations were shown to be active against various types of bacteria and in some cases, an increased anti-bacterial effect was observed. [63][64][65][66] But ILs are composed of a minimum of two ions (a cation and an anion) and both may impart biological activity to the resulting salt. This dual functionality inherent in ILs is rarely exploited, 67,68 and we have only recently published our first paper with the designed incorporation of two biologically active ions into an IL.…”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
“…In fact only recently, have specific ILs with biologically active ions been prepared and shown to retain their biological activity; specifically, IL salts of anti-bacterial quaternary ammonium cations were shown to be active against various types of bacteria and in some cases, an increased anti-bacterial effect was observed. [63][64][65][66] But ILs are composed of a minimum of two ions (a cation and an anion) and both may impart biological activity to the resulting salt. This dual functionality inherent in ILs is rarely exploited, 67,68 and we have only recently published our first paper with the designed incorporation of two biologically active ions into an IL.…”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
“…The significance of side-chain length on toxicity of ILs has been previously indicated and a general trend of increasing toxicity with increasing chain length, and consequently lipophilicity, was observed . However, some studies reported limited toxicity for various ILs with long side chains, containing fourteen, sixteen and more carbon atoms (García et al 2001;Pernak and Branicka 2003;Pernak and Chwała 2003;Cieniecka-Rosłonkiewicz et al 2005). Although not always raised by the authors, this was probably an artifact from limited solubility of these compounds, which were not bioavailable for microorganisms to cause toxic effect.…”
Section: Introductionmentioning
confidence: 86%
“…All ILs' were synthesized according to established methods (Bradaric et al, 2003;Cieniecka-Roslonkiewicz et al, 2005). An equivalent of tertiary phosphine was added dropwise to the appropriate alkylating reagent under nitrogen and stirred at a temperature rising from 30 to 200°C.…”
Section: Chemicalsmentioning
confidence: 99%